2023
DOI: 10.1039/d2ma01000c
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in organic-based radiative cooling materials: fabrication methods and thermal management properties

Abstract: Organic-based materials capable of radiative cooling have attracted widespread interest in recent years due to their ease of engineering and good adaptability to different application scenarios. As a cooling material...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 157 publications
0
12
0
Order By: Relevance
“…37,38 Therefore, it is crucial to consider proper moisture management in the design and installation of insulation panels. 39 When moisture is trapped within the hydrophilic structure, can cause a variety of issues, including the decay of the insulation panels. Additionally, the presence of moisture can increase the density of the aerogel over time, which can gradually deteriorate the thermal insulation properties of the panels.…”
Section: Resultsmentioning
confidence: 99%
“…37,38 Therefore, it is crucial to consider proper moisture management in the design and installation of insulation panels. 39 When moisture is trapped within the hydrophilic structure, can cause a variety of issues, including the decay of the insulation panels. Additionally, the presence of moisture can increase the density of the aerogel over time, which can gradually deteriorate the thermal insulation properties of the panels.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we calculate the conversion between the test time of ultraviolet aging test chamber and the outdoor illumination time according to the indicators provided by the equipment company [5] . Outdoor lighting conditions are not only related to seasons and regions.…”
Section: Discussionmentioning
confidence: 99%
“…Passive radiative cooling (PRC) has proven to be a promising electricity-free cooling strategy for dissipating heat of terrestrial objects through the atmospheric transparency window (8-13 μm) [1][2][3][4][5], and have attracted much attention for its potential of mitigating global warming [6] and the urban heat island effect [7,8]. Sub-ambient daytime cooling applications under 3 direct sunlight illumination is particularly attractive and challenging to achieve [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…These specialized polymers often incorporate additives, fillers, or surface modifications that enhance their radiative properties. Products based on these polymers can effectively radiate heat away from a surface, promoting cooling. , Specialized polymers can exhibit favorable RC properties due to their high thermal emissivity in the thermal IR spectrum. Key RC properties of specialized polymers are high emissivity, atmospheric window emissivity, low solar absorption, and material stability.…”
Section: Specialized Polymersmentioning
confidence: 99%
“…To facilitate RC, materials with specific properties which include the ability to reflect and emit in different λ are often used. Recent reviews of mostly optical aspects of RC materials can be found in refs , . These materials are mostly designed to have specific optical properties that enable high emissivity in the atmospheric window while reflecting or transmitting solar radiation in the visible and near-IR regions.…”
Section: Introductionmentioning
confidence: 99%